The Local Brain Abnormalities in Patients With Transient Ischemic Attack: A Resting-State fMRI Study - Lv, Yating; Li, Lingyu; Song, Yulin; Han, Yu; Zhou, Chengshu; Zhou, Dan; Zhang, Fuding; Xue, Qiming; Liu, Jinling; Zhao, Lijuan; Zhang, Cairong; Han, Xiujie (Frontiers in Neuroscience, 2019)
Abstract Background: Transient ischemic attack (TIA) is an important risk factor for stroke. Despite the transient episodes of clinical symptoms, brain alterations are still observed in patients with TIA. However, the functional mechanism of transient ischemia is still unclear. Here, we employed resting-state functional magnetic resonance imaging (rs-fMRI) to explore the functional abnormalities in patients with TIA. Methods: 48 TIA patients and 41 age- and sex-matched healthy controls (HCs) were enrolled in the study. For each participant, we collected rs-fMRI data and clinical/physiological/biochemical data. Amplitude of low frequency fluctuation (ALFF), regional homogeneity (ReHo) and degree centrality (DC) were then calculated. Two sample t-tests were performed to compare the ALFF, ReHo, and DC maps between the two groups. Furthermore, a correlation analysis was performed to explore the relationship between local brain abnormalities and clinical/physiological/biochemical characteristics tests in TIA patients. Results: Compared with the HCs, the TIA patients exhibited decreased ALFF in the left middle temporal gyrus, decreased DC in the triangular part of right inferior frontal gyrus, and no significant statistical difference in ReHo. No correlation was found between local abnormalities and clinical/physiological/biochemical scores in the patients with TIA. Conclusions: Collectively, these findings provide evidence for local brain dysfunctions in patients with TIA, which may help to understand the pathological mechanism of TIA and may help diagnose and guide therapeutic decisions for the disease.